CRIME IN MARRIAGE - Rizki Maulana; Dhiauddin Tanjung (Jurnal Hukum Samudra Keadilan, 2024)
Currently, the provision regarding the offence of adultery is regulated in Article 284 of the Criminal Code. One of the reasons for this regulation is to protect marriage from things such as vigilante actions based on adultery and the spread of disease, as well as other potentially damaging influences such as the rapidly growing prostitution industry which poses a threat to society. The punishment received by the perpetrator is a maximum imprisonment of 9 months in accordance with Article 284 paragraph (1) number 1 letter a of the Criminal Code. If your husband or wife has an affair, they, and others, are all responsible. The spouse of the person having the affair is also caught in the net by the provisions of this article. Article 284 of the KUHP defines adultery as an "offence of complaint", meaning that a complaint must come from the spouse of the adulterer before criminal proceedings can commence. In Islam, engaging in adultery carries heavy condemnation and guilt. Divorce is a legal option for infidelity and marital discord. Moreover, infidelity is also synonymous with adultery, a vice condemned by most religions.